2018
DOI: 10.1007/s00394-018-1754-6
|View full text |Cite
|
Sign up to set email alerts
|

Moderate egg consumption and all-cause and specific-cause mortality in the Spanish European Prospective into Cancer and Nutrition (EPIC-Spain) study

Abstract: This study shows no association between moderate egg consumption, up to 1 egg per day, and main causes of mortality in a large free-living Mediterranean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…The Japanese dietary pattern, Washoku, may be sufficient to avoid the influence of cholesterol by consumption of eggs. The correlation between consumption of eggs and cancer may also be a matter of concern, though not conclusive [162,163].…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese dietary pattern, Washoku, may be sufficient to avoid the influence of cholesterol by consumption of eggs. The correlation between consumption of eggs and cancer may also be a matter of concern, though not conclusive [162,163].…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Collaborative Cohort Study found that consumption of fish showed a significant inverse association with HCC mortality among participants without history of liver diseases 43 . Studies on associations between eggs and prognosis of cancers were inconsistent 39,43,44 . Patients in this study had a low consumption of egg (1 g/day), far below the recommendation for eggs.…”
Section: Discussionmentioning
confidence: 65%
“…43 Studies on associations between eggs and prognosis of cancers were inconsistent. 39,43,44 Patients in this study had a low consumption of egg (1 g/day), far below the recommendation for eggs. At low egg intake levels, increasing egg consumption may provide high-quality protein and essential micronutrients for patients with HCC.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, the question about the role of sex steroid hormones in milk in the development of prostate and testicular cancer in humans remains open. Additionally, high egg consumption is also associated with the occurrence of several cancers, including breast and prostate cancer [57], while there is no correlation between the consumption of up to one egg per day and any cause of mortality [58]. Although preventing cardiovascular disorders, a diet high in fi sh increases the risk of ovarian and endometrial cancer [59].…”
Section: Hormones In Food Of Animal Origin and Consumers' Healthmentioning
confidence: 99%